2007
DOI: 10.1038/sj.npp.1301629
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-Adrenoceptors in Memory Consolidation: β3-Adrenoceptors Act on Glucose Uptake and β2-Adrenoceptors on Glycogenolysis

Abstract: Noradrenaline, acting via b 2 -and b 3 -adrenoceptors (AR), enhances memory formation in single trial-discriminated avoidance learning in day-old chicks by mechanisms involving changes in metabolism of glucose and/or glycogen. Earlier studies of memory consolidation in chicks implicated b 3 -rather than b 2 -ARs in enhancement of memory consolidation by glucose, but did not elucidate whether stimulation of glucose uptake or of glycolysis was responsible. This study examines the role of glucose transport in mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 76 publications
1
56
0
Order By: Relevance
“…The same study showed that DAB induced memory impairment at specific times after training can be rescued by application of lactate or of the astrocyte-specific metabolic substrate acetate together with aspartate. These act as a precursor for oxaloacetate, which is needed because acetate alone cannot support pyruvate carboxylation [160, 164]. The glutamate precursor glutamine also rescued DAB induced memory impairments as well as the impairment induced by propranolol or by the glutamine synthetase inhibitor MSO.…”
Section: The Role Of Norepinephrine In Behavioral Responses and Adaptmentioning
confidence: 99%
“…The same study showed that DAB induced memory impairment at specific times after training can be rescued by application of lactate or of the astrocyte-specific metabolic substrate acetate together with aspartate. These act as a precursor for oxaloacetate, which is needed because acetate alone cannot support pyruvate carboxylation [160, 164]. The glutamate precursor glutamine also rescued DAB induced memory impairments as well as the impairment induced by propranolol or by the glutamine synthetase inhibitor MSO.…”
Section: The Role Of Norepinephrine In Behavioral Responses and Adaptmentioning
confidence: 99%
“…The effects of the metabolic inhibitors, 2-DG and DAB, that inhibit memory and glucose that facilitates memory when administered into the IMM (Gibbs and Summers, 2002b;Gibbs et al, 2006aGibbs et al, , 2007 were examined in the hippocampus to compare the temporal parameters in the two brain areas. Glucose (10 nmol/hemisphere) administered up to 15 min after weakly reinforced training facilitated memory consolidation (F (7, 107) ¼ 8.74; po0.001) (Figure 11a).…”
Section: -Ar Agonistsmentioning
confidence: 99%
“…The doses for glucose and 2-DG were selected from previous work (Gibbs and Summers, 2002b;Gibbs et al, 2007), and DAB was used at 0.1 nmol/ chick s.c. (Figure 12a). A dose of DAB of 0.3 nmol/chick was required to significantly impair memory (Figure 12a) (DAB, F (3, 52) ¼ 11.54; po0.001).…”
Section: -Ar Agonistsmentioning
confidence: 99%
“…A day old chick's (35-40 g) intermediate medial mesopallium and medial hyperstriatum ventral are not larger than an adult rat's (290-330 g) infralimbic cortex. However, microinjections into these targets with larger volumes (5 to 10 μl) did not cause tissue damages (Gibbs et al, 2008;Steele et al, 1996). Other examples for larger volumes are as follows; rat lateral ventricle microinjections at 10 μl volume (Wang et al, 2004), rat prefrontal cortex microinjections at 5-6 μl volumes (Sogabe et al, 2013).…”
Section: Discussionmentioning
confidence: 95%